PENERAPAN GAYA MAKEUP THAILAND PADA TATA RIAS WAJAH CIKATRI BERJERAWAT DITINJAU DARI ASPEK ESTETIKA - Ainur Friska Rahayu; Nia Kusstianti; Sri Dwiyanti; M.A. Hanny Ferry Fernanda (Program Studi Pendidikan Tata Rias, 2026)
This study aimed to determine the results of applying the Thailand makeup style to acne-scarred facial makeup in terms of aesthetic aspects. The study employed an experimental method with a quantitative approach using a One Shot Case Study design. The research subjects consisted of one model with acne-scarred skin and three observers who had competence in the field of cosmetology and makeup. Data were collected using an observation sheet covering skin preparation, acne scar correction techniques, application of Thailand makeup style, and final makeup results. The data were analyzed using descriptive statistics in the form of percentages. The results showed that the application of the Thailand makeup style on acne-scarred facial makeup achieved an average score of 74.96%, which was categorized as good. The level of acne scar concealment obtained an average score of 91.7%, which was categorized as very good. The findings indicate that the Thailand makeup style can improve facial aesthetics through a more even complexion, the use of contour and highlight to create facial dimensions, and eye makeup that provides visual focus on the face. However, this technique was found to be more effective in concealing skin discoloration than uneven skin texture caused by acne scars. Therefore, the Thailand makeup style can be considered an alternative corrective makeup technique to enhance the aesthetics of acne-scarred facial skin. Keywords: Corrective Makeup, Thailand Makeup, Facial Aesthetics, Acne-Scarred Skin, Color Correction.